Propuesta de mejora para el manejo y almacenamiento de sustancias químicas según el sistema globalmente armonizado (Aceites Morichal S.A.S) (2023)
Based on standards such as resolution 773 of 2021 or decree 1496 of 2018, which define the actions to be developed by employers for the implementation of the Globally Harmonized System (GHS) of Classification and Labeling of Chemicals in the workplace and other provisions on chemical safety are issued.